Length changes of Austrian glaciers in 2016/2017 - Gerhard Karl Lieb; Andreas Kellerer-Pirklbauer (PANGAEA, 2021)
Glacier length change data of 96 Austrian glaciers were collected for the period summer/autumn 2016 to summer/autumn 2017 (variable periods depending on specific measurement dates). The 95 monitored glaciers are well distributed over the glaciated mountain ranges of the Austrian Alps and consider both small and some of the largest (c.15 km^2) glaciers in Austria. Therefore, this sample is considered to be representative for all present-day glaciers in Austria. The monitored glaciers spatially extend from latitude 46°33 extquotesingleN to 47°30 extquotesingleN and longitude 10°04 extquotesingleE to 13°39 extquotesingle E. The data made available here comprise the glacier-length-change results for the glaciological year 2016-2017 and are based on a paper published in the official magazine of the Austrian Alpine Club named "Bergauf" (https://www.alpenverein.at/bk/bergauf/bergauf2018/Bergauf_2_2018/). These data are also stored in the database of the World Glacier Monitoring Service (WGMS) in Zurich, Switzerland (https://wgms.ch/). Glacier changes at the 96 glaciers was measured in two different ways. First, at 71 Austrian glaciers, the position of the glacier terminus was quantified for 2016 and 2017 by measuring the distance between distinct marked points in the proglacial area and the ice margin in clearly defined directions (azimuths). The difference of measured distances in 2016 and 2017 yields the glacier length change for one specific point. By calculating the arithmetic mean of several of such marked points at a given glacier, the glacier change value was obtained for this glacier. Second, at seven Austrian glaciers the position of the glacier terminus was quantified for 2016 and 2017 using Global Navigation Satellite System (GNSS) techniques or other geodetic instruments measuring the glacier terminus for both years and - based on this – calculating a glacier length change value. Furthermore, for five glaciers the change of the glacier position was qualitatively determined by photograph comparison. Finally, for 13 glaciers it was not possible to quantify glacier change rates for 2016-2017 due to missing data. The measurements were carried out by 20 different teams led by one or two investigators.9 Regarding the wider context, glacier length changes of Austrian Glaciers are measured annually within the framework of a monitoring program of the Austrian Alpine Club for more than 100 years. Measurements of length variations in Austria were started as early as 1878 at, for instance, Pasterze Glacier. Since that year, glaciological surveys have been carried out almost annually at this glacier representing one of the longest time series of continuous glacier monitoring worldwide. For more details regarding the glacier monitoring program of the Austrian Alpine Club visit https://www.alpenverein.at/portal/museum-archiv/gletschermessdienst/index.php (only in German).